Providing education and financial literacy about stock investment planning for SMK PGRI Pandaan students - Ery Sulistyorini; Isman Isman; Yesi Erpa Indah Sari; Maria Margaretha Bude (University of Merdeka Malang, 2022)
The potential for capital market investment development in Indonesia is very large. However, the growth in investment interest so far is still very low. Low investment interest in the capital market is caused by several obstacles, including lack of knowledge, information, and low education and literacy about investing in the capital market. The introduction of the right investment should be given to people who have productive age because it is considered a driver of the economy. Educational supplies and investment literacy have the potential to be developed for high school students, which in this service activity are carried out at SMK PGRI Pandaan. The reason is that students are of productive age and can qualify to invest in the capital market. Stock investment education and literacy activities carried out at SMK PGRI Pandaan are considered appropriate because the school's conditions lack facilities and information so the level of knowledge and skills of students related to stock investment is still relatively low. To achieve the target output of the activity, the methods used are lecture, practice, discussion, and question and answer. The training activities are carried out through Zoom Meetings because they are still in a state of the Covid-19 pandemic. This training activity resulted in the achievement of knowledge about stock investment, benefits, and risks as well as skills in how to trade shares.